The loading of C-type natriuretic peptides improved hemocompatibility and vascular regeneration of electrospun poly(ε-caprolactone) grafts. (1st October 2022) - Li, Jing; Zhuo, Na; Zhang, Jingai; Sun, Qiqi; Si, Jianghua; Wang, Kai; Zhi, Dengke
Abstract: As a result of thrombosis or intimal hyperplasia, synthetic artificial vascular grafts had a low success rate when they were used to replace small-diameter arteries (inner diameter < 6 mm). C-type natriuretic peptides (CNP) have anti-thrombotic effects, and can promote endothelial cell (EC) proliferation and inhibit vascular smooth muscle cell (SMC) over-growth. In this study, poly(ε-caprolactone) (PCL) vascular grafts loaded with CNP (PCL-CNP) were constructed by electrospinning. The PCL-CNP grafts were able to continuously release CNP at least 25 days in vitro . The results of scanning electron microscopy (SEM) and mechanical testing showed that the loading of CNP did not change the microstructure and mechanical properties of the PCL grafts. In vitro blood compatibility analysis displayed that PCL-CNP grafts could inhibit thrombin activity and reduce platelet adhesion and activation. In vitro cell experiments demonstrated that PCL-CNP grafts activated ERK1/2 and Akt signaling in human umbilical vein endothelial cells (HUVECs), as well as increased cyclin D1 expression, enhanced proliferation and migration, and increased vascular endothelial growth factor (VEGF) secretion and nitric oxide (NO) production. The rabbit arteriovenous (AV)-shunt ex vitro indicated that CNP loading significantly improved the antithrombogenicity of PCL grafts. The assessment of vascular grafts in rat abdominal aorta implantation model displayed that PCL-CNP grafts promoted the regeneration of ECs and contractile SMCs, modulated macrophage polarization toward M2 phenotype, and enhanced extracellular matrix remodeling. These findings confirmed for the first time that loading CNP is an effective approach to improve the hemocompatibility and vascular regeneration of synthetic vascular grafts. Statement of significance: Small-diameter (< 6 mm) vascular grafts (SDVGs) have not been made clinically available due to their prevalence of thrombosis, limited endothelial regeneration and intimal hyperplasia. The incorporation of bioactive molecules into SDVGs serves as an effective solution to improve hemocompatibility and endothelialization. In this study, for the first time, we loaded C-type natriuretic peptides (CNP) into PCL grafts by electrospunning and confirmed the effectiveness of loading CNP on improving the hemocompatibility and vascular regeneration of artificial vascular grafts. Regenerative advantages included enhancement of endothelialization, modulation of macrophage polarization toward M2 phenotypes, and improved contractile smooth muscle cell regeneration. Our investigation brings attention to CNP as a valuable bioactive molecule for modifying cardiovascular biomaterial. Graphical abstract: Image, graphical abstract